2008
DOI: 10.4161/cbt.7.7.6207
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of NF-κB and pro-inflammatory cytokines following administration of mucotoxic drugs

Abstract: Although changes in serum levels of NFkappaB, TNF, IL-1beta and IL-6 preceded histological changes in tissues, it was concluded that measurement of these factors was not useful in predicting mucosal damage because of the critical time constraints between detectable serun changes and the histological damage. This study highlighted the systemic effects of the drugs. Further studies are required to determine the possible relationships between different toxicities and determine how, once these links are known, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 16 publications
2
119
0
4
Order By: Relevance
“…[28,29], generated by stressed host cells, or exogenous pathogen-associated molecular patterns (PAMPs) [30][31][32] are recognized as being capable of activating the pattern recognition receptors (PRRs) [33] of the immune cells and as promoting the synthesis of inflammation mediators. Thus, any kind of tissue damage (pathogens [34,35], CRT [8,9] etc.) can induce a local [27,36] and systemic inflammatory response through circulating mediators ( Fig.…”
Section: Deteriorating Evolution Of Systemic Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,29], generated by stressed host cells, or exogenous pathogen-associated molecular patterns (PAMPs) [30][31][32] are recognized as being capable of activating the pattern recognition receptors (PRRs) [33] of the immune cells and as promoting the synthesis of inflammation mediators. Thus, any kind of tissue damage (pathogens [34,35], CRT [8,9] etc.) can induce a local [27,36] and systemic inflammatory response through circulating mediators ( Fig.…”
Section: Deteriorating Evolution Of Systemic Inflammationmentioning
confidence: 99%
“…can induce a local [27,36] and systemic inflammatory response through circulating mediators ( Fig. 1) [8,9,20]. Some Authors [37] postulated that anti-inflammatory mediators predominate within the bloodstream to avoid igniting new inflammatory foci, while their presence within tissues may not always be sufficient to prevent the initiation of a deleterious inflammatory response in various compartments [38].…”
Section: Deteriorating Evolution Of Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these clinical findings, recent in vivo research has identified elevated proinflammatory cytokines 7 and pathogenic bacteria 25 as hallmarks of CIGT. Importantly, proinflammatory cytokines 26 and pathogenic bacteria 27 exhibit modulatory effects on tight junction proteins and therefore may be responsible for changes in barrier integrity.…”
Section: Introductionmentioning
confidence: 99%
“…3 CIGT development is a multifactorial process characterized by dynamic biochemical interactions between chemotherapeutic agents and cellular constituents of the mucosa. [4][5][6] Recent research has focused on the molecular mechanisms that underpin CIGT, highlighting roles for apoptosis, 1 the immune system, 7 the gut microbiome, 8 and matrix metalloproteinases (MMPs). 9 More recently, intestinal tight junctions were proposed to play important roles in the pathophysiology of CIGT.…”
Section: Introductionmentioning
confidence: 99%